Geochemistry of Tierra Australis (TIA12-PB01C) peat core from Argentina - Thomas P Roland; Dmitri Mauquoy (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.